The daughter's seduction: Feminism and psychoanalysis - Gallop, Jane (Cornell University Press, 1982)
At the time this book was published in 1982, Jane Gallop was professor of French at Miami University; she has also written Intersections: A Reading of Sade with Bataille, Blanchot, and Klossowski. She wrote in the Introduction, "[the book] studies the relation between contemporary feminist theory and the psychoanalysis of Jacques Lacan... it enters into a network of problems: problems of sexual difference, of desire, of reading, or writing, of power, of family, of phallocentrism and of language... this book is ... a contribution to the sort of thinking it describes---that is, a contribution to French psychoanalytic feminist thought from the vantage point of these English-speaking shores." (p.11) She adds, "The book begins by calling into question certain feminist assumptions through the agency of Lacanian psychoanalysis. It ends by calling into question certain psychoanalytic positions through the agency of feminist writing." (p.15) She states that "[Freudian] Phallocentrism seems wrong to [Ernest] Jones: that is, immoral by virtue of being 'excessive, immoderate,' which is to say, unreconcilable with a 'sense of proportion.' The phallic disproportion brings him... to champion the claims of an 'underestimated' female sexuality to a more balanced, more proportionate estimate. His 'sense of proportion,' his spirit of fair play, will be sufficiently scandalized to provoke his only major departure from Freud's theory." (p. 16) She observes that in an article, "[Stephen] Heath begins by informing us that ... Lacan's 1972/73 seminar [is] devoted to 'what Freud expressly left aside... What does woman want?' ... Yet Lacan said nothing of devotion... Lacan speaks of a beginning... of a relation to this question: far from devoting himself to women he is simply at the stage of approach, first and rather aggressive encounter." (p. 43) This book will be of interest to feminists studying psychoanalysis, or to students of Lacan.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; thématiques; écriture des femmes*; états-unis